Safety and effectiveness of carbon nanoparticles suspension-guided lymph node dissection during thyroidectomy in patients with thyroid papillary cancer: a prospective, multicenter, randomized, blank-controlled trial - Zhao, Jingzhu; Wang, Junyi; Cheng, Ruochuan; Qin, Jianwu; Ai, Zhilong; Sun, Hui; Guo, Zhuming; Zhang, Xiaohua; Zheng, Xiangqian; Gao, Ming (Frontiers in Endocrinology, 2024)
Objective: This study aimed to evaluate the effectiveness and safety of carbon nanoparticles-guided lymph node dissection during thyroidectomy in patients with papillary thyroid cancer. Methods: Clinical trials consisted of two subgroups: unilateral lobectomy (UL; n=283) and total thyroidectomy (TT; n=286). From each subgroup, the patients were randomly assigned to two groups: the carbon nanoparticle group and control group. Primary endpoints included parathyroid hormone (PTH) levels, number of lymph nodes (LNs) detected, number of tiny lymph nodes detected, and recognition and retention of the parathyroid glands. Secondary endpoint was recognition and protection of the recurrent laryngeal nerve. Results: A total of 569 patients with PTC were recruited. There were no statistically significant differences in demographics between the carbon nanoparticles and control groups (P > 0.05). In the UL subgroup, there were no significant differences in PTH levels between the two groups at preoperative, intraoperative, and postoperative day one, and postoperative month one (P>0.05). There was no significant difference in the serum Ca 2+ levels between the two groups preoperatively and at postoperative month one (P>0.05). The number of lymph nodes dissected in the carbon nanoparticles group was significantly higher than that in the control group (P<0.0001). The detection rate of tiny lymph nodes in the carbon nanoparticles group was higher than that in the control group (P=0.0268). In the TT subgroup, there was no significant difference in PTH levels between the two groups at preoperative, intraoperative, and postoperative day one (P>0.05). However, the mean PTH level in the carbon nanoparticles group was significantly higher than that of the control group at postoperative month one (P=0.0368). There was no significant difference in the serum Ca 2+ levels between the two groups preoperatively and at postoperative month one (P>0.05). There were no significant differences between the two groups in the number of dissected LNs (P>0.05) or the detection rate of tiny lymph nodes (P>0.05). There were no significant differences between the two groups in terms of parathyroid preserved in situ and recurrent laryngeal nerve injury in the UL and TT subgroups. Conclusions: Carbon nanoparticles demonstrated efficacy and safety in thyroidectomy.